Double tuned filter design for harmonic mitigation in grid connected solar PV - Yong B.H.; Ramachandaramurthy V.K. (Institute of Electrical and Electronics Engineers Inc., 2023)
Renewable energy plays a significant part in the power generation revolution in line with the future smart grid focus. In Malaysia, one of the largest, clean and green energy produced is the solar PV energy. With obvious increase of penetration by renewable energies especially solar energy, in years to come the grid system is capable to self-sustain as micro grid without heavily depending from fossil fuel source. As the power flow will no longer be a one-way route generation, power quality issues arises from these interconnection can be very damaging to the grid and distribution assets if not handled well especially on harmonic issues. This paper presents the implementation of Double-Tuned filter for harmonic attenuation in a test case grid model. The design of the proposed filters is validated by simulation results in PSCAD software. The results show that the improved design meets the standards parallel to the THD and individual harmonic limits. © 2014 IEEE.